Isolation of Naegleria lustrarea n. sp. (Excavata, Discoba, Heterolobosea) from the feces of Ambystoma annulatum (Ringed Salamander) in Northwest Arkansas - Becker, Brian M; Banson, Idan; Walker, James M; Deshwal, Anant; Brown, Matthew W; Silberman, Jeffery D (The Journal of eukaryotic microbiology, 2024)
The salamander, Ambystoma annulatum, is considered a "species of special concern" in the state of Arkansas, USA, due to its limited geographic range, specialized habitat requirements and low population size. Although metazoan parasites have been documented in this salamander species, neither its native protists nor microbiome have yet been evaluated. This is likely due to the elusive nature and under-sampling of the animal. Here, we initiate the cataloguing of microbial associates with the identification of a new heterlobosean species, Naegleria lustrarea n. sp. (Excavata, Discoba, Heterolobosea), isolated from feces of an adult A. annulatum.
Keywords: Arkansas; Feces; FLA – free‐living amoeba; amphizoic; Ambystoma; Heterolobosea; endobiont; zvířata; feces; Naegleria; Phylogeny; fylogeneze; eukaryotic gut‐microbiome; amphibian; Animals